Alkyl and aryl dicationic derivatives of cyclic triphosphenium ions. - Dillon, K; Goeta, A; Howard, J; Monks, P; Shepherd, H; Thompson, A (2008)
Direct alkylation of cyclic triphosphenium ions by triflates to give di-ium dications is only possible for small organic substituents on the attacking reagent. The dicationic products are not intrinsically unstable, however, and in many instances they may be synthesised by an alternative route, pioneered by Schmidpeter and co-workers. These species may be readily identified in solution by (31)P NMR spectroscopy. The crystal and molecular structures of five such derivatives have been ascertained for the first time by single crystal X-ray diffraction at 120 K. The results confirm that normal single P-P bond lengths are present in the dications, in contrast with the monocationic parent cyclic triphosphenium ions, where structural determinations have shown that the P-P bond lengths are intermediate between single and double bonds.